Amomum jackliamii, A new zingiberaceae species from western Sarawak, Borneo - Jovita, E. Ripen; Stephen Teo, Ping; Meekiong, Kalu (Bjir Publications, 2023)
Amomum jackliamii, a new Zingiberaceae species is described herein. The new species is close to Amomum stenosiphon but this species has white prickly hairs towards the leaf tip at both edges of the leaf margin at the apex, adaxially surface reddish to dark green when matured. The leaves produce lemony smell and strong smell on the root when crushed white-cream flowers, the lip has a yellow centre bordered by two red lines, about 8.5 cm long, that gradually